1985
DOI: 10.1172/jci112060
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of vasopressin-stimulated water flow in toad bladder by phorbol myristate acetate, dioctanoylglycerol, and RHC-80267. Evidence for modulation of action of vasopressin by protein kinase C.

Abstract: The action of vasopressin (AVP) in transporting epithelia is mediated by cyclic AMP (cAMP), whereas its effects in hepatocytes are mediated by calcium and phosphoinositides. Based on our recent observation that AVP stimulates phosphoinositide turnover in toad bladder, we examined the role of calcium-phospholipid-dependent kinase (protein kinase C) as a modulator of AVP's hydroosmotic effect. Phorbol myristate acetate (PMA), which can substitute for diglyceride as an activator of protein kinase C, the diglyceri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 23 publications
(31 reference statements)
3
23
0
Order By: Relevance
“…Phorbol esters such as PMA enhance PGIE2 production in MDCK cells (20) and toad bladder epithelia (7). These findings are an important consideration in our studies since Stokes and Kokko have found that exogenous PGE2 inhibits net Na absorption and VT in the rabbit CCT (21).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Phorbol esters such as PMA enhance PGIE2 production in MDCK cells (20) and toad bladder epithelia (7). These findings are an important consideration in our studies since Stokes and Kokko have found that exogenous PGE2 inhibits net Na absorption and VT in the rabbit CCT (21).…”
Section: Discussionmentioning
confidence: 72%
“…Schlondorff and Levine have found evidence that protein kinase C activation with phorbol esters can modulate arginine vasopressin (AVP)-stimulated water flow in toad bladder by inhibiting cyclic AMP generation (7). Yanase and Handler have recently demonstrated that activation of protein kinase C with phorbol esters inhibits apical sodium transport of A6 epithelia (8), a cell line that shares many characteristics of the mammalian distal tubule.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of protein kinase C has been shown to inhibit AVP-stimulated water flow in the toad bladder (14) and in the isolated perfused rabbit cortical collecting tubule (15). Though a pre-cAMP site appears operant in the toad bladder (14), the predominant site of action of protein kinase C in both tissues is post-cAMP.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the other signaling limb, i.e., the effect of stimulation of PLC on cAMP generation, was not examined. Similarly, while activation of protein kinase C has been shown to inhibit AVP-stimulated water flow in the toad bladder (14) and in the rabbit cortical collecting duct (15), in neither tissue has the effect ofcAMP on hormonally stimulated PLC activity been examined. Accordingly, the present study was undertaken to examine bidirectional interactions between the AC and PLC signaling systems in a single cell type, the cultured rat inner medullary collecting tubule (RIMCT) epithelial cell.…”
Section: Introductionmentioning
confidence: 99%
“…Increased intracellular calcium and activation of PKC has been reported to inhibit AVP-induced water transport in rabbit CCD (5,50). There are several potential mechanisms by which increased intracellular calcium might inhibit AVP-stimulated water flow.…”
Section: Discussionmentioning
confidence: 99%